The hermeneutical self and an ethical difference intercivilizational engagement - Chung, Paul S., 1958- (Cambridge [England] : James Clarke, 2012)
In response to the religious and spiritual transition experienced in our modern world, Chung creates a postcolonial framework for inter-religious exchange, focussing on issues of interpretation, moral deliberation and ethical praxis. He investigates the relationship between hermeneutical theory and ethics and produces a new theory for intercivilizational dialogue, studying theological-philosophical theory of interpretation, ethics, the experience of cultural hybridity and inter-civilisational alliance, set within multiple horizons and diverse contexts.
3. Phemenology and Hermeneutics2. Interpretation and Life Connection; Part I; Hermeneutical Theory and Human Experience; 1. Interpretation and Experience; Introduction; Preface; Foreword; Acknowledgements.
Includes bibliographical references (pages 274-284) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Hermeneutics; Hermeneutics -- Religious aspects; PHILOSOPHY -- Epistemology; Hermeneutics; Hermeneutics -- Religious aspects; RELIGION / General; Electronic books